Photodermatosis and Photo protection in Metropolitan Traffic Police in Kathmandu city - Aryal, Eliz; Bhattarai, Sabina; Pokhrel, Govind; Shrestha, B. Sanju (International Journal of Occupational Safety and Health, 2018)
Background: Police officer serves a vital role in maintaining safety and serve are role model for discipline throughout the world, they are non–intentional type sun exposure(NISE).The objective of our present study was to evaluate photo protector practice, knowledge in response to Ultra violet Radiation ,Sunscreens and sun related photodermatosis. Methodology: A cross sectional study was conducted in traffic police officer at different locations at Kathmandu. Data was collected by using self-administered questionnaires and interviewed by Dermatologist to establish their knowledge and behaviour and practice in relation to ultra violet radiation and photo-protection. Result: Out of 265 participants, mean age was 27.1 years. Respondent with graduation and master degrees had knowledge and practice toward UVR, follow by higher secondary education. Regarding the practice for photo protection only 59.6% had knowledge about sunscreen, 39.6% knowledge about Ultraviolet Radiation and 24.9% had knowledge about Ultra Violet Index .Skin problem like melasma, premature wrinkles, and hardening of skin, polymorphic light eruption, burning foot syndrome, dermatophytes, and varicose vein. Conclusion: Traffic police officers showed good practices in term of wearing hat, clothes that cover most of the body parts but poor practice over sunscreen, UVR, UVI. Lectures & seminar regarding the awareness and photo protection practice should be recommended. With lack of awareness among police officers and providing sunscreen for free should be considered by Police authorities. Similarly lectures & seminar on sun protection should be provided in regularly.